Study of the Correlation Between Intestinal Health and Prevalence of Coccidiosis in Broiler Chickens of Brazilian Agribusinesses Between the Years 2015 and 2016 - Gazoni, F.L.; Adorno, F.C.; Matte, F.; Malta, T.; Felin, M.R.; Urbano, T.; Zampar, A.; Hernandez-Velasco, X.; Tellez , G. (International Journal of Poultry Science, 2017)
Objective: The objective of this study was to analyze the correlation between the lesions caused by Eimeria and the prevalence of coccidiosis and other alterations encountered in the gastrointestinal tract of broilers produced in Brazil from 2015-2016. Materials and Methods: Intestinal health assessments were conducted in 72 broiler integration businesses in Brazil, totaling 2,200 birds in two rearing phases: 1 (age 12-21 days) and 2 (age 22-40 days). Intestinal aspects, lesion scoring and oocyst counts of Eimeria maxima (E. maxima) were analyzed. Results: E. acervulina was the most prevalent species (mean of 13.5%) in both rearing phases, followed by E. maxima (5.6%) and E. tenella (2.2%). E. maxima was present in 30.4% of mucosal scrapings performed during phase 1, which represents a subclinical coccidiosis of 706.98% (7.07 times) in relation to clinical coccidiosis. In phase 2, E. maxima was found in mucosal scrapings of 34.3% of the birds, representing a subclinical coccidiosis of 497.11% (4.98 times) in relation to clinical coccidiosis. In the comparative analysis between the periods, subclinical coccidiosis struck 112.83% (1.13 times) more broilers in phase 2 in relation to stage 1. Subclinical coccidiosis struck a significant number of broilers in the Brazilian flocks and was correlated with various factors of intestinal health reduction. Conclusion: It was concluded that monitoring is of paramount importance to knowing the intestinal health status of poultry flocks because microscopic E. maxima is prevalent (32.3%) and correlated to factors that reduce intestinal health.